Assessment of the Conceptual and Moral Factors on the Outcome of Wars: An AI Perspective - Yesilyurt, Gurkan (Cranfield University, 2024)
3MT contribution to the Defence and Security Doctoral Symposium 2023
Keywords: AI on social science; DSDS23; DSDS23 3MT